Results of viscobubble deep anterior lamellar keratoplasty after failure of pneumatic dissection. Issue 3 (23rd December 2017) - Scorcia, Vincenzo; De Luca, Valentina; Lucisano, Andrea; Carnevali, Adriano; Carnovale Scalzo, Giovanna; Bovone, Cristina; Busin, Massimo
Abstract : Aim: To report the outcomes of bubble formation obtained by means of intrastromal injection of ophthalmic viscoelastic device (OVD) after failure of pneumatic dissection for deep anterior lamellar keratoplasty (DALK). Methods: DALK was performed in 140 keratoconic eyes of 130 patients by injecting air and OVD only secondarily, after pneumatic dissection had failed; the bubble formation rates after air and OVD injection were recorded; complications, best spectacle-corrected visual acuity (BSCVA) and corneal tomographic parameters were evaluated 3 months, 6 months and 12 months postoperatively, as well as after complete suture removal. Results: Air injection created a big bubble in 106/140 eyes (75.71%); OVD injection was not attempted in 4 eyes (perforation during cannula insertion n=2; air bubble burst n=2) and created a big bubble in 28 of the remaining 30 eyes (93.33%, 20% of the total). Manual dissection was required in 2/30 eyes (6.66%, 1.42% of the total) after failed OVD-assisted dissection. Deep folds, interface opacity and reduced BSCVA were noted in both eyes after failed OVD-assisted dissection. BSCVA was statistically better after pneumatic-assisted than after OVD-assisted dissection (P 0.01) only up to 3 months postoperatively; no statistically significant differences were recorded between the two techniques at later examinations. Conclusion: Intrastromal injection of OVD after failed pneumatic dissection increases considerably the success rate of bubble formation (from 75.71% to 95.71% in our series); however, when bubble formation fails, infiltration of OVD into the residual stroma makes manual dissection particularly challenging and causes severe interface haze resulting in poor visual outcomes.